Poly(2‐alkyl‐2‐oxazoline)‐Heparin Hydrogels—Expanding the Physicochemical Parameter Space of Biohybrid Materials. Issue 22 (20th September 2021) - Hahn, Dominik; Sonntag, Jannick M.; Lück, Steffen; Maitz, Manfred F.; Freudenberg, Uwe; Jordan, Rainer; Werner, Carsten
Abstract: Poly(ethylene glycol) (PEG)‐glycosaminoglycan (GAG) hydrogel networks are established as very versatile biomaterials. Herein, the synthetic gel component of the biohybrid materials is systematically varied by combining different poly(2‐alkyl‐2‐oxazolines) (POx) with heparin applying a Michael‐type addition crosslinking scheme: POx of gradated hydrophilicity and temperature‐responsiveness provides polymer networks of distinctly different stiffness and swelling. Adjusting the mechanical properties and the GAG concentration of the gels to similar values allows for modulating the release of GAG‐binding growth factors (VEGF165 and PDGF‐BB) by the choice of the POx and its temperature‐dependent conformation. Adsorption of fibronectin, growth of fibroblasts, and bacterial adhesion scale with the hydrophobicity of the gel‐incorporated POx. In vitro hemocompatibility tests with freshly drawn human whole blood show advantages of POx‐based gels compared to the PEG‐based reference materials. Biohybrid POx hydrogels can therefore enable biomedical technologies requiring GAG‐based materials with customized and switchable physicochemical characteristics. Abstract : Hydrogels made of different poly(2‐alkyl‐2‐oxazolines) (POx), crosslinked with the glycosaminoglycan (GAG) heparin, are shown to provide distinctively different swelling and temperature responsiveness, allowing for a temperature‐controlled release of GAG‐binding signaling molecules and a far‐reaching modulation of further cell‐instructive properties. The newly established biohybrid POx‐GAG hydrogel platform is therefore envisioned to enable various advanced biomedical technologies.